DESIGN OF AN AUTOMATIC DECORATIVE PLANTS WATERING SYSTEM USING THE BLYNK APPLICATION BASED ON MICROCONTROLLER AND SOLAR PANEL - Darmawan, Isra' Nuur; Wahjudi, Dody; Septia Nugroho, Rudi; Kholistianingsih (Journal of Electronic and Electrical Power Applications, 2023)
Just like humans, plants need water for their growth and development. Plants should not have a lack or excess of water, soil that lacks water makes plants develop slowly and in ornamental plants makes the plants look not fresh and wilted and vice versa, plants that have too much water also make the plants unhealthy and can even cause the plants to die. The aim of the research is to design and build an automatic plant watering device that can be controlled remotely via an Android smartphone application, to determine the response speed of the tool in executing commands given by the user via the Android application, to find out the benefits of solar panels in order to save electricity usage in watering. Ornamental Plants by determining tool needs from various literature and collecting data from internet references and books as well as data that is needed and analyzing the components needed to make tools. The results of the research produced points, namely success in designing an automatic plant watering device based on the Wemos D1 R1 Microcontroller with the Blynk Application on Android as a remote control, the results of the characterization of the type of sensor used, namely the Soil sensor. Senor Soil has an accuracy of 98.65% and a standard deviation of ±0.14 for air temperature measurements and an accuracy of 98.72% and a standard deviation of ±0.38 for air humidity readings, the updated data on the Blynk Application is in accordance with the data sent by the Wemos D1 R1 Microcontroller. There is a time difference of 1 second between the data transmission time by the Wemos D1 R1 Microcontroller and the data reception time by the Blynk Application. The automatic plant watering tool that has been designed has a response speed of 2 seconds, starting from the time the user gives the command via the Blynk Application on the Smartphone until the device start the watering process